(untitled) (Scientific journal of the Fergana State University, 2023)
The article emphasizes the poet’s skill in using words through the analysis of Abdulla Oripov’s poem "Autumn Dreams". The poet’s ability to break a deep philosophical thought into lines is studied with the help of visual expressions and tools, poetic art.